ASSESSMENT OF THE N-TERMINAL COLLAGEN III-TYPE PROPEPTIDE IN PATIENTS WITH CHRONIC HEART FAILURE AND METABOLIC SYNDROME - O. M. Drapkina; E. V. Zyatenkova (Кардиоваскулярная терапия и профилактика)
Development and progress of chronic heart failure (CHF) are faster in obesity, lipid and carbohydrate metabolism disorders. The liver presentation of metabolic syndrome (MS) is the non-alcoholic fatty liver disease (NAFLD). Comorbidity of NAFLD and cardiovascular diseases leads to increase of cardiovascular risk and dramatically influences outcomes and prognosis of CHF. The key element of pathogenesis and the factor of progression of CHF is myocardium remodeling. N-terminal collagen III-type propeptide (PIIINP) is regarded as promising in the role of myocardium remodeling and CHF development.Aim. To assess the relation of PIIINP and clinical signs of CHF, condition of myocardium and liver condition in CHF patients with MS. Material and methods. Totally 77 patients included with CHF. In all the diagnosis was confirmed with qualitative measurement of brain natriuretic peptide (NT-proBNP). Main group (MG) included 39 patients with CHF and MS. Controls (CG) included 38 patients with CHF, but not MS. The severity of clinical manifestation of CHF was evaluated, and patients functioning status. All patients underwent clinical and biochemical blood tests, electrocardiography. The heart chambers were measured, myocardium walls thickness and thickness of epicardial fat via echocardiography. To all patients the calculations were done with Fatty Liver Index (FLI), NAFLD Fibrosis Score (NFS).Results. The level of PIIINP in MG — 3,3±1,5 mcg/L, in CG — 2,3±1,3 mcg/L (p=0,00046). In statistical analysis there were significant relations of laboratory data and PIIINP: uric acid level (r=0,37; p=0,001); glucose level (r=0,29; p=0,011). Glomerular filtration rate (r=-0,37; p=0,002); value of FLI (r=0,47; p=0,001); NFS (r=0,31; p=0,007); between echocardiography and PIIINP: epicardial fat thickness (r=0,33; p=0,004); interventricular septum thickness (r=0,33; p=0,003); left ventricle myocardium mass (r=0,36; p=0,002); right atrium sizes (r=0,34; p=0,043); left atrium sizes (r=0,35; p=0,034); end-diastolic size of the left ventricle (r=0,31; p=0,006); relation Е/А (r=0,28; p=0,013); relation Е/е (r=0,24; p=0,038).Conclusion. Application of PIIINP measurement in clinical practice makes it to reveal those with CHF and MS who have structural and functional changes of myocardium even at early stages of the disease. Measurement of PIIINP in CHF and MS patients makes it to find patients with liver disorders and to select patients for further investigation taking into consideration comorbidities.